Fully-integrated inductive switched-mode DC-DC converters - Sun, Yin (Nanyang Technological University, 2021)
This Ph.D. research program pertains to single-phase (fully-integrated) and multi-phase (both fully-integrated and non-fully-integrated) inductive DC-DC converters. The general objectives are analytical investigations, proposal of a power optimization methodology, and a novel modulation scheme, and the ensuing designs of these DC-DC converters to improve one or more of the following attributes over the state-of-the-art: high power-efficiency, small form-factor, low input harmonics, and low output noise. For the single-phase converter, the objectives include the modeling and power analysis for power-efficiency optimization, where the inductor is a bonding wire whose Q is moderate (ranging from 6-30), and a proposed power optimization methodology. The intended model and analysis are comprehensive where the ensuing proposed power-efficiency optimization accounts for bothAC and DC power losses of the bonding wire inductor in a fully-integrated converter, and that can be applied to both continuous conduction mode and discontinuous conduction mode operations. Our model further encompasses analytical power loss expressions of the power transistors and their gate drivers. Our proposed model is verified with >90% accuracy through simulations and on the basis of physical measurements. We provide applications of our model in three perspectives: bonding wire length, power losses and their ensuing optimization, and different CMOS processes. Our proposed model is useful as it provides valuable insights into the design of fully-integrated converters and the mechanisms for power-efficiency. For the multi-phase converter, the objectives include the proposal of a randomized modulation scheme, and analysis and demonstration of its efficiency. The proposed scheme is denoted "Randomized Wrapped-Around Pulse Position Modulation scheme withWrapped-Around Phase-Shifts (RWAPPM+WAPS)". To the best of our knowledge, this is the first-ever application of a randomized modulation scheme for a multi-phase converter. Our proposed scheme involves randomizing the pulse positions in the first phase to spread out the harmonic power, wrapping around the pulse shifts in other phases to reduce the overlapped pulses and hence mitigating the output noise, and if necessary, augmenting additional phases to further mitigate the output noise. We derive an analytical expression to predict the input current spectrum and show that our proposed RWAPPM+WAPS simultaneously mitigates both the input current harmonics and the output noise. For example, for a three-phase converter employing our proposed RWAPPM+WAPS, the peak input current spectral power and output noise ripple are simultaneously significantly reduced over the same converter employing a conventional randomized modulation scheme—by 3.6 dB (equivalent to 3.3x) and 200.3 mV (equivalent to 9.9x), respectively. Put simply, the proposed scheme is unique and advantageous as it mitigates both input harmonics and output noise for multi-phase converters.